2014
DOI: 10.1371/journal.pone.0113215
|View full text |Cite
|
Sign up to set email alerts
|

Regulator of G-Protein Signaling 18 Controls Both Platelet Generation and Function

Abstract: RGS18 is a myeloerythroid lineage-specific regulator of G-protein signaling, highly expressed in megakaryocytes (MKs) and platelets. In the present study, we describe the first generation of a RGS18 knockout mouse model (RGS18-/-). Interesting phenotypic differences between RGS18-/- and wild-type (WT) mice were identified, and show that RGS18 plays a significant role in both platelet generation and function. RGS18 deficiency produced a gain of function phenotype in platelets. In resting platelets, the level of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 40 publications
7
22
0
Order By: Relevance
“…S2). These results confirmed previous reports documenting the stimulatory role of Rgs18 in megakaryocytic differentiation (Delesque-Touchard et al, 2014;Louwette et al, 2012).…”
Section: Antagonistic Functions Of Rgs18 In Erythroid and Megakaryocysupporting
confidence: 92%
See 1 more Smart Citation
“…S2). These results confirmed previous reports documenting the stimulatory role of Rgs18 in megakaryocytic differentiation (Delesque-Touchard et al, 2014;Louwette et al, 2012).…”
Section: Antagonistic Functions Of Rgs18 In Erythroid and Megakaryocysupporting
confidence: 92%
“…protein overexpression). As per previous reports (Delesque-Touchard et al, 2014;Louwette et al, 2012), inhibition of Rgs18 similarly retarded megakaryocytic differentiation of fetal liver progenitors cultured in vitro ( Fig. 2) and differentiation of the murine cell line L8057 induced with 12-O-tetradecanoylphorbol-13-acetate (TPA) (Fig.…”
Section: Antagonistic Functions Of Rgs18 In Erythroid and Megakaryocysupporting
confidence: 86%
“…Consistently, it was previously shown that knockdown of RGS18[24,25], RGS10[26] or mutation of the RGS binding site on Gαi[27] results in increased platelet reactivity. At this ISTH conference, Gupta et al confirmed that knockdown of RGS10 results in a gain of platelet function, in particular in response to stimulation by the second wave mediators, ADP and TxA 2 [28].…”
Section: Classical Hemostasis – Balancing Platelet Adhesiveness In CIsupporting
confidence: 77%
“…RGS18 negatively modulates the function of G-protein-coupled receptors (GPCRs). RGS18 makes platelets less sensitive to activation (30,31). Since PLD2 can be activated downstream of GPCRs (32), it is conceivable that the increase in RGS18 is a compensatory response to some of the effects of PLD2 overexpression.…”
Section: Localization Of Wnt1-inducible Signaling Pathway Protein 1mentioning
confidence: 99%